Theological Exclusivism of the Khawarij: A Threat to Islamic Moderation in the Modern Era - Ahmad, Muhammad Rasyidi; Kusnadi, Asep; Baharuddin, Baharuddin (International Journal of Social and Political Sciences, 2025)
This study addresses the persistence of religious radicalism in contemporary Muslim societies, particularly in Indonesia, where pluralism and social cohesion are challenged by exclusive, takfiri, and anti-state interpretations of Islam. In this context, the theological legacy of the Khawarij is important because its doctrines of excommunication, absolutism, and legitimized violence continue to influence modern extremist narratives. The study aims to analyze the genealogy of Khawarij theology, compare its ideological characteristics with Hizbut Tahrir Indonesia and Jemaah Islamiyah, and assess its implications for Islamic moderation in the modern era. This research employs a qualitative library research approach using secondary data from classical Islamic texts, contemporary books, scholarly journal articles, research reports, religious documents, and credible digital sources. Data were collected through systematic literature review and analyzed using content analysis, supported by source and perspective triangulation to ensure validity. The findings show that Khawarij theology is characterized by takfir, rigid literalism, hostility toward dissent, rejection of illegitimate rulers, and justification of violence. These elements reappear in contemporary radical groups, although expressed through different strategies, with HTI emphasizing ideological-political mobilization and Jemaah Islamiyah employing violent methods. The study concludes that Khawarij-style theological exclusivism remains a serious threat to Islamic moderation and should be addressed through historically grounded deradicalization and stronger promotion of wasathiyah Islam. Therefore, strengthening inclusive theology, tolerance, and contextual religious interpretation is essential for preserving peace within Indonesia's plural society today.